Strategi Komunikasi dalam Mempromosikan Nilai-Nilai Kebangsaan di Era Media Sosial - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Isma Nur Hanifa; Alfiansyah Habib Arrokhim; Muhammad Nafi’ul Umam (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study examines communication strategies in promoting national values ​​in the era of social media which has a very important role in building collective awareness and strengthening the sense of national unity. Social media, as a fast and broad means of communication, offers challenges as well as opportunities for efforts to strengthen nationality. In this context, an effective communication strategy must utilize digital platforms to disseminate inclusive national messages, prioritize tolerance, and strengthen national identity. The approaches used can be in the form of utilizing visual content, narratives that touch emotions, and collaboration with influencers and public figures to create a greater impact. In addition, it is important to pay attention to the aspects of speed and accuracy of information, so that the message conveyed is not easily distorted or misinterpreted. This study uses method a qualitative approach with a case study design to understand communication strategies in promoting national values ​​in the era of social media. The qualitative approach was chosen because it allows researchers to explore in depth the communication phenomena that occur in society, especially on social media. This study discusses various communication techniques and models that can be used to convey national values ​​to the younger generation, as well as the challenges faced in managing information amidst the diversity of opinions on social media. The results of this study to contribute to the development of more effective communication strategies in promoting national values ​​in the digital era.